2016
DOI: 10.3390/ma9070593
|View full text |Cite
|
Sign up to set email alerts
|

Binary Alkali-Metal Silicon Clathrates by Spark Plasma Sintering: Preparation and Characterization

Abstract: Abstract:The binary intermetallic clathrates K 8-x Si 46 (x = 0.4; 1.2), Rb 6.2 Si 46 , Rb 11.5 Si 136 and Cs 7.8 Si 136 were prepared from M 4 Si 4 (M = K, Rb, Cs) precursors by spark-plasma route (SPS) and structurally characterized by Rietveld refinement of PXRD data. The clathrate-II phase Rb 11.5 Si 136 was synthesized for the first time. Partial crystallographic site occupancy of the alkali metals, particularly for the smaller Si 20 dodecahedra, was found in all compounds. SPS preparation of Na 24 Si 136… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…A peculiar feature of Rb 8 B 8 Si 38 (and also K 7 B 7 Si 39 ) is the predominant substitution of silicon atoms on position 16 i (Si2). The site typically shows the shortest interatomic framework distances, e.g., in the related binary silicon clathrates K 8– x Si 46 or Rb 6.15 Si 46 , and is thus best suited for accommodating the small boron atoms. Position 6 c (Si1), , which is preferred by larger substitution atoms like transition metals, is avoided by boron as the resulting local configuration and interatomic distances would be unfavorable for sp 3 -hybridized boron atoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A peculiar feature of Rb 8 B 8 Si 38 (and also K 7 B 7 Si 39 ) is the predominant substitution of silicon atoms on position 16 i (Si2). The site typically shows the shortest interatomic framework distances, e.g., in the related binary silicon clathrates K 8– x Si 46 or Rb 6.15 Si 46 , and is thus best suited for accommodating the small boron atoms. Position 6 c (Si1), , which is preferred by larger substitution atoms like transition metals, is avoided by boron as the resulting local configuration and interatomic distances would be unfavorable for sp 3 -hybridized boron atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of lattice parameters (Figure , Table S3) reveals reduced values for ternary clathrate-I borosilicides in relation to their binary analogs, ,, e.g., the unit cell of Rb 8 B 8 Si 38 ( a = 9.9583(1) Å) is significantly smaller than that of Rb 6.15 Si 46 ( a = 10.27188(6) Å) , in which the dodecahedral cages are almost empty. The lattice parameter is connected to the framework contacts of position 16 i and the metal-network distances in the small cages (Figure ) by the relation As boron substitution and rubidium defects mainly affect positions, which are located on the body diagonal of the unit cell, the shortening of the framework distances d (16 i –16 i ) in the ternary phase (Table S3) goes along with a pronounced contraction of the lattice.…”
Section: Resultsmentioning
confidence: 99%
“…Scherf et al have demonstrated that allo -Ge can also be electrochemically prepared from Li 12 Ge 17 [138]. On the other hand, macroscopic single crystals of clathrate-II Na 24 Si 136 [139] and other silicon clathrates [140] are obtained by field assisted sintering of Na 4 Si 4 at 600 °C under uniaxial pressure (so-called spark plasma sintering). Directed growth of Na 24 Si 136 at the anode and accumulation of metallic Na at the cathode is suggestive of an influence of the electric current and solid-state electrochemical reaction.…”
Section: Discussionmentioning
confidence: 99%
“… Lattice parameters a vs average network distances trued of the ternary M x B y Si 46− y ( M =K, Rb, Cs) [6,7] and binary M x Si 46 ( M =Na, K, Rb, Cs, Sr, Ba) [12–19] clathrate‐I phases. Open symbols denote compounds obtained under high‐pressure conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the reduction of the contact distance between the four‐connected B and Si atoms at position 16 i effectively reduce the lattice parameters in comparison to those of binary clathrate‐I silicides M x Si 46 ( M =Na, K, Rb, Cs, Sr, Ba) [12–19] . This corresponds to an overcompensation of the volume contribution of the alkali metal atoms by deformation of the dodecahedral cages [7] …”
Section: Resultsmentioning
confidence: 99%